Clinical characteristics and treatment response of treatment requiring retinopathy of prematurity (ROP) in Big Premature Infants in Turkiye: BIG-ROP Study Group Report No 2 (BIG-ROP STUDY) - Sengul Ozdek; Zafer Cebeci; Ayşegül Çömez; Nihat Sayın; Merih Çetinkaya; Ozlem Şahin; Ahmet Yagmur Bas; Esin Koc; İbrahim Murat Hirfanoglu; Guner Karatekin; Kadir Serafettin Tekgunduz; Servet Ozkiraz; et al. (BMJ Open Ophthalmology)
Objective This study evaluated the clinical characteristics and treatment outcomes of bigger premature infants treated for retinopathy of prematurity (ROP).Methods A retrospective, multicentre study analysed data from 33 ROP centres in Türkiye. Infants with gestational ages (GA) of 32–37 weeks and birth weights (BW) >1500 g who required ROP treatment were included. Patient demographics, clinical details, treatments, responses and complications were recorded. Descriptive statistics were calculated after excluding cases with missing or erroneous data.Results The study included 365 eyes of 365 infants. The average GA at birth was 33±1 weeks, with a mean BW of 1896±316 g. Of these, 83.6% had type 1 ROP, and 16.4% had aggressive ROP (A-ROP). Treatment-requiring ROP (TR-ROP) occurred at an average postmenstrual age of 39.0±4.6 weeks. Among 170 infants with TR-ROP at their first exam, 81.2% were screened at 4 weeks postpartum. Reactivation of ROP was observed in 5.4% of the primary laser photocoagulation (LPC) group and 23.9% of the primary anti-vascular endothelial growth factor (VEGF) group (p<0.001). Reactivation and progression to stage 4–5 were more frequent in A-ROP cases (p=0.012; p=0.008). The need for additional treatment was significantly higher in cases of A-ROP, zone 1 disease or stage 4–5 disease (p<0.001). Anti-VEGF therapy demonstrated superior single-treatment success rates in A-ROP eyes compared with laser LPC (85.7% vs 60%, p=0.03). Infants requiring additional treatments also had higher rates of respiratory distress syndrome (RDS), maternal premature rupture of membranes (PROM) and non-ophthalmological surgical interventions (p<0.05).Conclusion Bigger premature infants in low and middle-income countries should be screened earlier than 4 weeks after birth. A-ROP, zone 1 disease and stage 4–5 disease have higher reactivation risks. Primary anti-VEGF therapy was associated with a greater need for retreatment. Maternal PROM, RDS and surgical interventions also increase retreatment risk. Limitations include retrospective design and lack of smaller preterm comparisons, potentially limiting generalisability.